2018
DOI: 10.1016/j.neo.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Interferon-Stimulated Gene 20 by Thyroid Hormone Enhances Angiogenesis in Liver Cancer

Abstract: Thyroid hormone, 3,3′,5-triiodo-l-thyronine (T3), mediates several physiological processes, including embryonic development, cellular differentiation and cell proliferation, via binding to its nuclear thyroid receptors (TR). Previous microarray and Chromatin immunoprecipitation (ChIP)-on-ChIP analyses have revealed that interferon-stimulated gene 20 kDa (ISG20), an exoribonuclease involved in the antiviral function of interferon, is up-regulated by T3 in HepG2-TR cells. However, the underlying mechanisms of IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…In addition, ISG20 mRNA expression is up-regulated in HCC tumour compared to adjacent non-tumour tissues. These results, which are compatible with a previous study showing overexpression of ISG20 mRNA in cancerous compared to adjacent tissues [ 13 ], indicate that ISG20 is involved in the development of HBV-related HCC. Differential expression patterns of ISG20 have been shown in the biopsies of various malignancies, including virus-related cancers like glioblastoma and HCC [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, ISG20 mRNA expression is up-regulated in HCC tumour compared to adjacent non-tumour tissues. These results, which are compatible with a previous study showing overexpression of ISG20 mRNA in cancerous compared to adjacent tissues [ 13 ], indicate that ISG20 is involved in the development of HBV-related HCC. Differential expression patterns of ISG20 have been shown in the biopsies of various malignancies, including virus-related cancers like glioblastoma and HCC [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, our study shows that ISG20 levels are strongly associated with liver function tests in patients with HCC, also indicating that ISG20 may contribute to the pathogenesis of HBV-related HCC. In support of our observations, a previous study has shown that ISG20 overexpression in HCC tumours was correlated with clinical parameters, such as vascular invasion, AFP levels and tumour sizes, as well as with poorer recurrence-free survival in HCC patients [ 13 ]. In addition, ISG20 levels are correlated with AFP levels in LC patients and are different between CHB patients with AFP levels lower and higher than 5 IU/mL as well as between LC patients with AFP levels lower and higher than 25 IU/mL.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…45 ISG20 was reported as a pro-angiogenic factor in liver cancer. 46 On the other hand, IRF9 was termed as a key factor for eliciting the anti-proliferative activity of interferon alpha. 18,47 Additionally, NLRC5 is a critical player in maintaining immune surveillance.…”
Section: Discussionmentioning
confidence: 99%